Engineering Environment-Mediated Multi-Agent Systems - Weyns, Danny (Springer, 2017)
This book constitutes the thoroughly refereed proceedings of the International Workshop on Engineering Environment-Mediated Multi-Agent Systems, EEMMAS 2007, held in Dresden, Germany, in October 2007, in conjunction with ECCS 2007, the European Conference on Complex Systems